A new synthesis approach of hierarchical MoS2 nanoflakes toward hydrogen evolution in both acidic and alkaline media. Issue 94 (9th November 2022) - Liu, Changhai; Min, Shengkang; Yao, Yanhua; Shakouri, Mohsen; Zhang, Lei; Hu, Yongfeng; Chen, Zhidong
Abstract : Ultrathin MoS2 flakes were prepared using a synergistic liquid phase precipitation method by applying ultrasound and microwaves simultaneously for a highly efficient HER under both alkaline and acidic conditions. Abstract : Herein, ultrathin MoS2 flakes were prepared using a synergistic liquid phase precipitation method by applying ultrasound and microwave simultaneously. At 10 mA cm 2 of electric current density, the MoS2 electrocatalysts' passing points are 176 mV and 154 mV respectively in acidic and alkaline electrolytes. This research provides a new synthetic method and potential opportunity in the design and preparation of multiple synergistic high-efficiency electrocatalysts.